2017
DOI: 10.1016/j.compscitech.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear vibration and postbuckling of functionally graded graphene reinforced porous nanocomposite beams

Abstract: The nonlinear free vibration and postbuckling behaviors of multilayer functionally graded (FG) porous nanocomposite beams that are made of metal foams reinforced by graphene platelets (GPLs) are investigated in this paper. The internal pores and GPL nanofillers are uniformly dispersed within each layer but both porosity coefficients and GPL weight fraction change from layer to layer, resulting in position-dependent elastic moduli, mass density and Poisson's ratio along the beam thickness. The mechanical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(75 citation statements)
references
References 45 publications
0
75
0
Order By: Relevance
“…Several experimental evidences in literature, have revealed that the behavior of micro-structures is size-dependent [2][3][4][5]. Thus, a large number of works has been recently published to conceive novel structural solutions, systems, and devices, while adopting different types of reinforcement phase, such as graphene nanoplatelets [6][7][8][9][10][11][12][13][14], or carbon nanotubes [15][16][17][18][19]. Among a large variety of numerical strategies, higher order theories represent the most useful tool for the investigation of the static and dynamic response of materials at different scales [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental evidences in literature, have revealed that the behavior of micro-structures is size-dependent [2][3][4][5]. Thus, a large number of works has been recently published to conceive novel structural solutions, systems, and devices, while adopting different types of reinforcement phase, such as graphene nanoplatelets [6][7][8][9][10][11][12][13][14], or carbon nanotubes [15][16][17][18][19]. Among a large variety of numerical strategies, higher order theories represent the most useful tool for the investigation of the static and dynamic response of materials at different scales [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Ritz method and Timoshenko beam theory, the authors in Refs. [24,25] studied the free vibration, elastic buckling and the nonlinear free vibration, post-buckling performances of FGP beams, respectively. The uniaxial, biaxial, shear buckling and free vibration responses of FGP-GPLs were also investigated by [26] based on the first-order shear deformation theory (FSDT) and Chebyshev-Ritz method.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Ritz method and Timoshen theory, the authors in refs. [24] and [25] studied the free vibration, elastic buc the nonlinear free vibration, post-buckling performances of FGP beams, resp The uniaxial, biaxial, shear buckling and free vibration responses of FGP-G also investigated by [26] based on the first-order shear deformation theory (FS Chebyshev-Ritz method. Additionally, to investigate the static, free vibra buckling of FGP-GPLs, [27] utilized IGA based on both FSDT and the third-or deformation theory (TSDT).…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [29] carried out nonlinear bending and thermal postbuckling analyses of functionally graded graphenereinforced composite laminated beams resting on an elastic foundation and suggested that the functionally graded graphene reinforcement and temperature change have pronounced impacts on the nonlinear bending and thermal postbuckling behaviours. Kitipornchai and his coauthors [30,31] demonstrated that the incorporation of a small amount of GPLs can remarka-…”
Section: Accepted Manuscriptmentioning
confidence: 99%